The Correlation Between Preparedness and Burden among Family Caregivers of Cancer Patients Undergoing Chemotherapy - Permatasari, Arum Diah; Ike Wuri Winahyu Sari (Jurnal Keperawatan, 2024)
As a result of the treatment that requires extended time, family caregivers, therefore, demand preparedness, and more than often the treatment process becomes a burden. This study aimed to determine the correlation between the preparedness and the burden among family caregivers of cancer patients undergoing chemotherapy in Yogyakarta. This study is a descriptive correlative design using a cross-sectional approach. A total of 51 family caregivers of cancer patients undergoing chemotherapy were obtained using a purposive sampling technique. The questionnaires used are the Indonesian version of The Preparedness for Caregiving Scale and the Indonesian version of the Caregiver Reaction Assessment. The data in this study were analyzed using the Spearman Rank correlation test. The results of this study indicate that there is a significant correlation between the preparedness and the burden among family caregivers of cancer patients undergoing chemotherapy in Yogyakarta (p-value <0.001) and a correlation coefficient of -0.710 which shows a strong correlation. Health care professionals require to ensure that family caregivers have the right resources and support so they are prepared to care for their loved ones. This preparedness is useful to reduce the burden they feel in the process of caring for cancer patients.